Effects of internal strain and external pressure on electronic structures and optical transitions of self-assembled InxGa1−xAs/GaAs quantum dots : an experimental and theoretical study - Wen, Yuan (2013)
The optical emissive transitions from the ground and excited states of the self-assembled InxGa1−xAs/GaAs quantum dots (QDs) at room temperature were experimentally measured as a function of the external hydrostatic pressure by means of the confocal micro-photoluminescence technique. The ground state transition is very weak under zero external pressure and the photoluminescence is dominant by the excited state transition. However, the intensity of the ground state transition monotonically increases with increasing the external pressure and eventually become the dominant transition. Their pressure coefficients (PCs) were determined to be 6.8 and 7.1 meV/kbar, respectively, which were astonishingly smaller than those of GaAs bulk and the InGaAs/GaAs reference quantum well. The emission peak from the higher order excited states had a much smaller PC (∼0.5 meV/kbar). The influence of the built-in strain and external hydrostatic pressure on the electronic structures and optical transitions of various InxGa1−xAs/GaAs QDs was theoretically investigated by using the eight-band k·p method. Good agreement between the theoretical and experimental results was achieved, firmly revealing that the internal built-in strain in the dot system is mainly responsible for the experimental findings.